Furthering the Understanding of Wechsler Adult Intelligence Scale-Fourth Edition Factor Structure in a Clinical Sample. Issue 1 (2nd January 2021) - Merz, Zachary C.; Van Patten, Ryan; Hurless, Nicole; Grant, Alexandra; McGrath, Andrew B.
Abstract: The Wechsler Adult Intelligence Scale, Fourth Edition (WAIS-IV) is a commonly administered battery for assessing intellectual and cognitive abilities. Despite its popularity, construct validation studies primarily utilize the WAIS-IV normative sample rather than ecologically-valid clinical samples. The current study expands the literature on the validity of WAIS-IV by testing a bifactor model in such a sample. We examined archival data from 300 concurrent psychological evaluations performed at a university-based community clinic. Participants received the full WAIS-IV standard battery. Consistent with recent literature, confirmatory factor analyses (CFAs) favored a direct hierarchical model, where the g factor has a direct influence on WAIS-IV subtest performance and index scores explain only modest degrees of residual variance. Results challenge traditional intelligence nosologies and suggest consideration of a two-step method of WAIS-IV interpretation in clinical samples, whereby the Full Scale IQ score (FSIQ) score is examined first and individual subtest scores are analyzed second.